EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TEKNIK SHAPING UNTUK MEREDUKSI PERILAKU PROKRASTINASI AKADEMIK SISWA SMP - Shagita, Putri Chitasya; Afrilianto, M; Renata Manuardi, Ardian (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
The aim of this research is to assess the effectiveness of group guidance using a shaping approach to reduce academic procrastination behavior among students who fail to complete academic assignments. Group guidance that uses shaping techniques aims to help modify negative behavior into positive behavior by changing initial behavior into final behavior, thus showing the expected or desired behavior. This research uses a Mix Method or a combination of quantitative data and qualitative data using the Explanatory Sequential Design research design. Quantitative data processing techniques use questionnaires, while qualitative data is processed using observation, interviews and documentation studies. Using a purposive sampling procedure, the subjects in this research were ten students. Based on the findings showing that the research hypothesis was accepted, group guidance assisted by shaping techniques succeeded in reducing students' academic procrastination behavior, obtained t-count = -21.124 with a significance level (2-tailed) of 0.000 < 0.05. Specifically, there were variations in the level of academic procrastination behavior before and during group guidance treatment.